Advanced assessment of beam-induced background at a muon collider. (10th November 2021) - Collamati, F.; Curatolo, C.; Lucchesi, D.; Mereghetti, A.; Mokhov, N.; Palmer, M.; Sala, P.
Abstract: Renewed international interest in muon colliders motivates the continued investigation of the impacts of beam-induced background on detector performance. This continues the effort initiated by the Muon Accelerator Program and carried out until 2017. The beam-induced background from muon decays directly impacts detector performance and must be mitigated by optimizing the overall machine design, with particular attention paid to the machine detector interface region. In order to produce beam-induced background events and to study their characteristics in coordination with the collider optimization, a flexible simulation approach is needed. To achieve this goal we have chosen to utilize the combination of LineBuilder and Monte Carlo FLUKA codes. We report the results of beam-induced background studies with these tools obtained for a 1.5 TeV center of mass energy collider configuration. Good agreement with previous simulations using the MARS15 code demonstrates that our choice of tools meet the accuracy and performance requirements to perform future optimization studies on muon collider designs.